2004
DOI: 10.1523/jneurosci.5016-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Learning Modifies Subsequent Induction of Long-Term Potentiation-Like and Long-Term Depression-Like Plasticity in Human Motor Cortex

Abstract: Learning may alter rapidly the output organization of adult motor cortex. It is a long-held hypothesis that modification of synaptic strength along cortical horizontal connections through long-term potentiation (LTP) and long-term depression (LTD) forms one important mechanism for learning-induced cortical plasticity. Strong evidence in favor of this hypothesis was provided for rat primary motor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
489
10
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(557 citation statements)
references
References 37 publications
47
489
10
11
Order By: Relevance
“…This LTP-like increase in MEP amplitude shows tight similarities to cellular LTP because it is associative, input specific, and blocked by dextromethorphan, a non-competitive NMDAR antagonist (Stefan et al, 2002;Stefan et al, 2000;Wolters et al, 2003). Furthermore, PAS LTP -induced LTP-like plasticity interacts homeostatically with prior or subsequent motor learning (Elahi et al, 2013;Jung and Ziemann, 2009;Kang et al, 2011;Rosenkranz et al, 2007;Stefan et al, 2006;Ziemann et al, 2004), indicating its mechanistic importance in learning processes.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This LTP-like increase in MEP amplitude shows tight similarities to cellular LTP because it is associative, input specific, and blocked by dextromethorphan, a non-competitive NMDAR antagonist (Stefan et al, 2002;Stefan et al, 2000;Wolters et al, 2003). Furthermore, PAS LTP -induced LTP-like plasticity interacts homeostatically with prior or subsequent motor learning (Elahi et al, 2013;Jung and Ziemann, 2009;Kang et al, 2011;Rosenkranz et al, 2007;Stefan et al, 2006;Ziemann et al, 2004), indicating its mechanistic importance in learning processes.…”
Section: Introductionmentioning
confidence: 77%
“…In slice preparations of rat motor cortex (M1), LTP induction depends on disinhibition by application of a synaptic GABAAR antagonist and can be disrupted by NMDAR blockade (Aroniadou and Keller, 1995;Castro-Alamancos et al, 1995;Fritsch et al, 2010;Hess et al, 1996). At the systems level of human M1, LTP-like plasticity, indexed by a long-term increase in motor-evoked potential (MEP) amplitude, can be induced by paired associative stimulation (PAS LTP ) (Cooke and Bliss, 2006;Müller-Dahlhaus et al, 2010;Stefan et al, 2002;Stefan et al, 2000;Ziemann et al, 2004). This LTP-like increase in MEP amplitude shows tight similarities to cellular LTP because it is associative, input specific, and blocked by dextromethorphan, a non-competitive NMDAR antagonist (Stefan et al, 2002;Stefan et al, 2000;Wolters et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although both healthy and depressed subjects showed significant improvement in the rotor pursuit task, motor learning was comparatively impaired in depressed subjects. The lack of correlation between motor learning and PAS test results may be considered surprising as motor learning is considered at least partially reliant on LTP in the primary motor cortex (Ziemann et al, 2004). However, very few studies have found a significant relationship between motor learning outcomes and results of brain stimulation tests of motor cortex plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that repeated sessions of NIBS can increase the duration of the effects (Nyffeler et al, 2006;Meinzer et al, 2014). However, repeated plasticity-inducing paradigms can also attenuate the effects of subsequent stimulation (Ziemann et al, 2004). In this context, synaptic connections potentiated by the initial plasticity paradigm are rendered less able to do so with subsequent stimulation (indeed the synaptic connections become more responsive to inhibitory paradigms -a concept referred to as metaplasticity (Turrigiano, 1999)).…”
Section: Other Considerationsmentioning
confidence: 99%